Програма та методика експериментальних досліджень зношування деталей шестеренних насосів - В'юник, Ольга Володимирівна; Вьюник, Ольга Владимировна; Viunyk, Olha; Сєрий, Ігор Сергійович; Серый, Игорь Сергеевич; Sieryi, Ihor; Смєлов, Андрій Олександрович; Смелов, Андрей Александрович; Smielov, Andrii (My University, 2020)
UK: Ефективність роботи сільськогосподарської техніки залежить, головним чином, від її надійності. Працездатність і ресурс техніки в значній мірі визначаються інтенсивністю зношування деталей тертя. Від матеріалу і покриття трібоспряжень залежить зносостійкість і довговічність вузлів тертя при експлуатації. В статті наведено програму і методику експериментальних досліджень впливу епіламних покриттів на зносостійкість деталей насосу НШ-К. Представлена методика мікрометраж-них досліджень деталей та методика визначення функціональної залежності між структурними параметрами технічного стану насосу, які обумовлюють об’ємні витрати робочої рідини та впливають на об’ємний коефіцієнт подачі насосу. Описано порядок проведення стендових випробувань. Наве-дені вимірювані параметри, інструменти, прилади та обладнання для проведення експерименталь-них досліджень. RU: Эффективность работы сельскохозяйственной техники зависит, главным образом, от ее надежности. Работоспособность и ресурс техники в значительной степени определя-ются интенсивностью износа деталей трения. От материала и покрытия трибосопряжений зависит износостойкость и долговечность узлов трения при эксплуатации. В статье приведены программа и методика экспериментальных исследований влияния епиламних покрытий на износостойкость деталей насоса НШ-К. Представлена методика микрометражних исследований деталей и методика определения функциональной зависимости между структурными параметрами технического состояния насоса, которые обусловливают объемный расход рабочей жидкости и влияют на объемный коэффициент подачи насоса. Описан порядок проведения стендовых испытаний. Приведены измеряемые параметры, инструменты, приборы и оборудование для проведения экспериментальных исследований. EN: The efficiency of agricultural machinery depends mainly on its reliability - the ability to perform given functions with minimal labor costs and material resources for a long time. The efficiency and resource of agricultural machinery are largely determined by the intensity of wear of friction parts. The practice shows that 80-90% of machine parts fail due to wear. By choosing the right material and coating of the triboconjugation, you can significantly increase the wear resistance and durability of the friction units during operation. From the finish processing of parts depends not only the initial running, but also the subsequent intensity of wear during operation. One of the main advantages of the finishing antifriction non-abrasive treatment is the relative simplicity and versatility of the method, which allows the use of this method in a large machine-building enterprise with mass production, and in a small motor transport enterprise. This work is part of research on improving the post-repair durability of friction units of gear pumps by reducing wear of parts during the run-in period. The article presents the program and methods of experimental studies of the effect of epilam coatings on the wear resistance of gear pump parts. The method of micrometric research of pump parts and the method of determining the functional relationship between the structural parameters of the technical condition of the pump, which determine the volumetric flow rate of the working fluid and affect the volumetric flow rate of the pump. The procedure for conducting bench tests is described. Also the measured parameters, tools, devices and the equipment for carrying out experimental researches are given. Schemes of measurement of details of the gear pump are presented. The proposed program and methods of experimental research will determine the significance of the influence of epilam coatings on the wear resistance of pump parts.
Программа и методика экспериментальных исследований влияния епиламних покрытий на износостойкость деталей насоса
Program and methods of experimental studies of the effect of epilam coatings on the wear resistance of pump parts
Keywords: програма; методика; шестеренний насос; дослідження; вимірювання; вимірювальні інструменти; експеримент; программа; методика; шестеренный насос; исследования; измерения; измерительные инструменты; эксперимент; program; technique; gear pump; research; measurements; measuring instruments; experiment